Effect of Renal Denervation for the Management of Heart Rate in Patients With Hypertension: A Systematic Review and Meta-Analysis - Li, Le; Xiong, Yulong; Hu, Zhao; Yao, Yan (Frontiers in Cardiovascular Medicine, 2022)
Objective: The effect of renal denervation (RDN) on heart rate (HR) in hypertensive patients had been investigated in many studies, but the results were inconsistent. This meta-analysis was performed to evaluate the efficacy of RDN on HR control. Methods: PubMed, EMBASE, Cochrane and ClinicalTrials.gov were searched until September 2021. Randomized controlled trials (RCTs) or non-RCTs of RDN in hypertensive patients with outcome indicators including HR were included. Weighted mean difference (WMD) was calculated for evaluating the changes in HR from baseline using fixed-effects or random-effects models. The Spearman correlation coefficients was used to identify the relationship between the changes of HR and systolic blood pressure (SBP). Results: There were 681 participants from 13 individual studies were included in the current meta-analysis. This study showed that RDN could reduce office HR in hypertensive patients with WMD = -1.93bpm (95% CI: -3.00 to -0.85, p <0.001). And 24 hour-HR and daytime HR were also decreased after RDN (WMD = -1.73 [95% CI: -3.51 to -0.31, p = 0.017] and -2.67 [95% CI: -5.02 to -0.32, p = 0.026] respectively), but nighttime HR was not influenced by RDN (WMD = -2.08, 95% CI: -4.57 to 0.42, p = 0.103). We also found that the reduction of HR was highly related to the decrease of SBP (r = 0.658, p < 0.05). Conclusion: RDN could reduce office, 24-hour and daytime HR, but does not affect nighttime HR. And the effect is highly associated with BP control.